Contribution to the study on Triculinae snail group (Pomatiopsidae - Mollusca) in Tay Nguyen highland, Vietnam - Hai, Ho Thanh; Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
Based on taxonomical analysis of snails collected from streams belonging to Srepok River, two new species belonging to genus Pseudotricula Dang et Ho, 2006 are recorded. These snails can berepresentative populations of subfamily Triculinae - Pomatiopsidae existing in Tay Nguyen Highland, central Vietnam that located in watershed area of Mekong river system.Genus Pseudotricula Dang et Ho, 2006 was established based on type species Pseudotricula undulataDang et Ho, 2006. Up to now, the new genus Pseudotricula Dang et Ho seems to be characterized for small streams in mountainous area, having 9 species, including these two new species.In 1992, Ponder W. F. (1992) has established genus Pseudotricula Ponder, 1992 with type species Pseudotricula eberhardi Ponder n. sp., found in a cave stream at Tasmania (Australia). According to the shell description given by this author [14], the genus Pseudotricula Ponder seems to be clearly different from the genus Pseudotricula Dang et Ho, 2006. By shell structure, as well as, by cave living conditions of Pseudotricula eberhardi Ponder, 1992, the type species of this genus (in type locality at Tasmania, Australia).  However,  conforming  to  the  International  Code  of  Zoological  Nomenclature               (ICZN), Pseudotricula Dang et Ho, 2006 must be considered as a junior homonym of the genus Pseudotricula Ponder, 1992. Therefore, by ICZN, the generic name of Pseudotricula Dang et Ho, 2006 must be eliminated and replaced by the new name Vietricula Dang et Ho, 2008, proposed by the authors. Hence, Pseudotricula undulata Dang et Ho, 2006 - type species of the genus Pseudotricula Dang et Ho that to beconsidered as the type species of the genus Vietricula Dang et Ho, 2008 (ICZN, 2000, Articles 678, 727).Based on analysis of snail specimens, two new species Vietricula serepoki Dang et Ho sp. n. and V. laki Dang et Ho sp. n. are also described in this paper.